2017
DOI: 10.18632/oncotarget.18139
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal kinesin motor KIFC1 participates in facilitating proper cell division of human seminoma

Abstract: C-terminus kinesin motor KIFC1 is known for centrosome clustering in cancer cells with supernumerary centrosomes. KIFC1 crosslinks and glides on microtubules (MT) to assist normal bipolar spindle formation to avoid multi-polar cell division, which might be fatal. Testis cancer is the most common human cancer among young men. However, the gene expression profiles of testis cancer is still not complete and the expression of the C-terminus kinesin motor KIFC1 in testis cancer has not yet been examined. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 46 publications
1
43
0
Order By: Relevance
“…Findings were validated using BC fresh tissues and paraffin‐embedded specimens from our center. Results showed that KIFC1 was upregulated at both the mRNA and protein levels in BC tissues, consistent with the expression pattern of KIFC1 in other reported tumors . We investigated the relationship between KIFC1 expression and the clinicopathological features of patients with BC who had undergone radical cystectomy by performing IHC on 152 BC specimens.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Findings were validated using BC fresh tissues and paraffin‐embedded specimens from our center. Results showed that KIFC1 was upregulated at both the mRNA and protein levels in BC tissues, consistent with the expression pattern of KIFC1 in other reported tumors . We investigated the relationship between KIFC1 expression and the clinicopathological features of patients with BC who had undergone radical cystectomy by performing IHC on 152 BC specimens.…”
Section: Discussionsupporting
confidence: 77%
“…To date, KIFC1 has been reported to be overexpressed in various cancers. Xiao et al suggested that KIFC1 facilitated the proper cell division of a human seminoma. Other groups have reported that KIFC1 promoted hepatocellular carcinoma epithelial–mesenchymal transition (EMT) and metastasis through gankyrin/AKT signaling .…”
Section: Introductionmentioning
confidence: 99%
“…KIFC1 plays an important physiological role in the vesicular and organelle trafficking, spermiogenesis and oocyte development [59,60,61,62,63]. Furthermore, KIFC1 is widely expressed in cancer cells and may be essential for the bi-multipolar mitotic division of cancer cells but is dispensable in ordinary somatic cells, which qualifies KIFC1 as an excellent target in cancer therapy [29,64,65,66,67,68,69,70]. Direct KIFC1 inhibitors including AZ82, CW069 and transcription inhibitor PJ34 are readily available and have shown promising results in vitro and in vivo [68].…”
Section: Discussionmentioning
confidence: 99%
“…In human, a minus-end-directed motor KIFC1 in the Kinesin-14 family is known for its centrosome clustering in multi-centrosome cells and managing multi-polar spindles into pseudo-bipolar spindles to avoid multi-polar division [ 146 ]. KIFC1 is strongly expressed in cancer cells and result in numerous cancer types including testis cancer in man [ 147 , 148 ]. Furthermore, KIFC1 motor plays important roles in cancer cell division, which usually possesses more than two centrosomes and thus measured to be a new-generation chemotherapy target for cancer [ 149 , 150 ].…”
Section: Introductionmentioning
confidence: 99%